MICROBIAL SHIFTS ARE ASSOCIATED WITH PATIENT-REPORTED SYMPTOMS IRRESPECTIVE OF MUCOSAL INFLAMMATION IN PEDIATRIC PATIENTS WITH INFLAMMATORY BOWEL DISEASE. (21st January 2021) - Hellmann, Jennifer; Ta, Allison; Haslam, David; Lake, Kathleen; Bezold, Ramona; Jackson, Kimberly; Bonkowski, Erin; Andersen, Heidi; Dirksing, Kelsie; Ollberding, Nicholas; Denson, Lee
Abstract: Objectives: Inflammatory bowel diseases (IBD), including Crohn's disease (CD) and ulcerative colitis (UC), are characterized by an aberrant host response to intestinal microbiota causing mucosal inflammation and gastrointestinal symptoms. Patient reported outcome measures (PROs) are increasingly utilized in clinical care and research. Our study aim was to determine if fecal microbial shifts were associated with PROs in children and young adults with IBD. Methods: A longitudinal prospective single center study of 93 patients tested for association between fecal microbial shifts, mucosal inflammation as measured by fecal calprotectin, and self-reported symptoms including diarrhea, rectal bleeding, and abdominal pain. For CD, abdominal pain and diarrhea determined disease activity or overall PRO. For UC, diarrhea and rectal bleeding were used. Fecal calprotectin and shotgun metagenomic sequencing were performed on all samples. Demographic and clinical characteristics (Table 1) were incorporated into a negative binomial mixed-effects model in "R" to identify differentially abundant species by PRO and fecal calprotectin. Metabolic pathways were mapped using the HUMAnN2 pipeline and compared to overall PRO, individual symptoms and fecal calprotectin level. Results: In 70 CD patients with 244 stool samples, there was no association between symptoms and fecal calprotectin. In 23 UC patients with 76 stool samples, increased fecal calprotectin was associated with rectal bleeding (OR 4.93 [1.18, 20.64], p=0.03). Examination of differentially abundant species in those with self-reported active UC showed increased Klebsiella species and reduced Bacteroides. Conversely, UC patients with fecal calprotectin < 100 µg/gm had reduction in Klebsiella and increase in Bifidobacteria and Bacteroides (Figure 1). Analysis of differentially abundant species in those with abdominal pain in CD showed increase in Haemophilus and reduction in Bacteroides . No microbial shifts were identified in CD patients in association with overall PRO, diarrhea, nor with fecal calprotectin < 250 µg/gm. Metabolic pathway analysis showed no differences in those with CD. In UC patients, increases in sulfoglycolysis and ornithine biosynthesis were associated with overall PROs. Conclusions: Fecal microbial shifts including decreased commensals such as Bacteroides correlate with UC patient symptoms. Increased fecal calprotectin level was associated with rectal bleeding in these patients, but not diarrhea. In CD, there was no association with fecal calprotectin and symptoms, and microbial shifts were detected in association with abdominal pain. Similarly, metabolic pathways differed relative to patient-reported symptoms in UC, but not in CD. Data suggests that microbial shifts may directly contribute to symptoms in children and young adults with IBD.